2006
DOI: 10.1038/emm.2006.79
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of gangliosides expression during the differentiation of embryonic and mesenchymal stem cells into neural cells

Abstract: Stem cells are used for the investigation of developmental processes at both cellular and organism levels and offer tremendous potentials for clinical applications as an unlimited source for transplantation. Gangliosides, sialic acid-conjugated glycosphingolipids, play important regulatory roles in cell proliferation and differentiation. However, their expression patterns in stem cells and during neuronal differentiation are not known. Here, we investigated expression of gangliosides during the growth of mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 29 publications
0
57
3
Order By: Relevance
“…GD2 has previously been reported to be a potential marker of bone marrow-derived MSCs [55], but our results do not support this finding, since we did not observe GD2 (composition S2H2N1) at all in MSCs, but rather in osteoblasts derived from them. Human periodontal bone marrow MSCs have been reported to express GM1 [56], which was found also in the present study by MS/MS fragmentation, whereas after neuronal differentiation both GM1 and GT1b were detected [56]. In contrast to the present study, no other gangliosides, like GM3/GD3, could be detected [56].…”
Section: Discussioncontrasting
confidence: 56%
“…GD2 has previously been reported to be a potential marker of bone marrow-derived MSCs [55], but our results do not support this finding, since we did not observe GD2 (composition S2H2N1) at all in MSCs, but rather in osteoblasts derived from them. Human periodontal bone marrow MSCs have been reported to express GM1 [56], which was found also in the present study by MS/MS fragmentation, whereas after neuronal differentiation both GM1 and GT1b were detected [56]. In contrast to the present study, no other gangliosides, like GM3/GD3, could be detected [56].…”
Section: Discussioncontrasting
confidence: 56%
“…It has recently been demonstrated that the cell surface glycan heparan sulfate (HS) contributes to self-renewal and differentiation of mESCs by regulating BMP, Wnt, and FGF signaling [21,[27][28][29]. The expression patterns of several other cell surface glycans have now been described in undifferentiated and differentiated mESCs and hESCs [30][31][32][33][34]. However, although these glycans may be involved in the regulation of the signaling required for ESC self-renewal, with the exception of HS, their functional roles have not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiated Caco-2 cells contained more GD 3 and polar, complex gangliosides than undifferentiated Caco-2 cells. Human colostrum and differentiated human embryonic stem cells also contain high amounts of GD 3 and polar, complex gangliosides (22,41) . GD 3 and polar gangliosides may play a role in tight-junction formation (EJ Park, ABR Thomson and MT Clandinin, unpublished results), intestinal barrier integrity and the expression of proteins involved in digestion and absorption (42,43) .…”
Section: Discussionmentioning
confidence: 99%
“…The GM 3 :GD 3 ratio of mature rat small intestine is 26, similar to the ratio of 19·8 observed in mature milk (18,53) . For neonatal rat small intestine, the GM 3 :GD 3 ratio has not been determined; however, it is known that neonatal tissues decrease in GD 3 content and increase in GM 3 content during development (21,22,41) . Although the ganglioside composition changes are similar during rat intestine development, lactation and oncogenic transformation of colon cells, further ganglioside analysis work should be completed with infant bowel to determine changes in the GM 3 :GD 3 ratio during development and look at the degree of change in GM 3 and GD 3 levels.…”
Section: Discussionmentioning
confidence: 99%